Exercises in probability : - Chaumont, Loic (Cambridge University Press, 2003)
Probability theory has recently become more important as an area of study and research. This set of exercises can be used for classroom teaching or independent study and will help students reach the level where they can begin to tackle current research. It includes outline answers to all the problems and numerous references to the literature.